The Dynamics of Islamic Culture during the Abbasid Caliphate: An Intellectual Historical Perspective on the Role of Bayt al-Hikmah - Muhammad Zaki; Nurzena Nurzena (Mandalika Journal of Business and Management Studies, 2026)
This study explores the cultural dynamics of Islamic civilization during the Abbasid Caliphate, with particular emphasis on the strategic contribution of Bayt al-Hikmah to the intellectual development of the global scholarly tradition. The investigation focuses on the institutional mechanisms through which this establishment integrated external intellectual legacies with Islamic principles, thereby producing a dynamic civilizational synthesis. This research employs a qualitative historical approach with an intellectual history perspective to examine the role of Bayt al-Hikmah in the transmission, development, and institutionalization of knowledge during the Abbasid period. Data were collected through a comprehensive review of primary and secondary historical sources, including classical manuscripts, historical records, and recent scholarly literature. The collected data were analyzed through source criticism, thematic classification, and interpretive historical analysis. The findings indicate that political and material support from the Abbasid caliphs served as a crucial catalyst for the expansion of intellectual productivity, positioning Bayt al-Hikmah as a driving force behind the transformation of the Islamic world into an international center of scientific advancement. The study further reveals that the large-scale translation movement and the inclusive intellectual environment fostered the assimilation of diverse scientific traditions, contributing significantly to the advancement of philosophy, medicine, mathematics, and astronomy. This study concludes that Bayt al-Hikmah functioned not merely as a repository of literature but as an institutional foundation for fostering intellectual inclusivity and sustaining scholarly innovation. Theoretically, the research contributes new insights to cultural historiography by highlighting the importance of formal institutions in ensuring the continuity of knowledge production and innovation amid the challenges of the modern era.